Two Pioneer Programs in Studies of the Future. - Winthrop, Henry (Science Education)
The article discusses two pioneer programs in studies relating to advancements in science and technology in the U.S. Scientific and technological changes make their impact on society that necessitate the creation of new institutions to deal with and control these very conditions. The complex systems created by the numerous social components and processes, which science and technology brings often require an understanding of systems theory and the systems approach, computer programming and cybernetics. The Schools of Engineering of San Jose State College has instituted an interdisciplinary major in the form of a Master's degree in Cybernetic Systems. A project known as The Man-Made World was created to provide high school students with an understanding of the impact of technology upon the modern world.